(untitled) (Journal of University of Babylon for Engineering Sciences, 2021)
The urban population is one of the main reasons for the increase in urban area, this will lead to a change in situation of the population. The most important conclusion is that the year 2017 recorded a large gap between the inhabited and uninhabited land in favor of uninhabited land, that there are large areas have not been used and expand to future potential growth. However, this gap does not give us the green light, it urban land use functions. Planning connects between population growth and urban growth and both will lead to desirable urban growth within the master plan, however, lack of planning leads to undesirable urban growth outside the scope of the master plan. The growing gap between urban growth and population growth will produce the undesirable change in urban functions, such as unsustainable and non-standard urban land use. The aim of this research is to create a positive and balanced positive effect between urban growth and population growth under the influence of the sustainable urban criterion and a functional distribution of the various urban land uses. The equation of simple population growth and the sustainable urban standard and the descriptive historical approach used to link urban growth with population growth, through the accurate forecast of the population is using the population growth equation for years to come may reach ten years. Urban population is distributed on the basis of the uses of urban land, which are balanced by the criteria of using local or regional urban land that respond to the social, economic and cultural means the urban planning is not sure responds to the requirements of population growth, especially there are the problem of housing, health, electricity, water, transport, noise and environmental pollution suffer from most developing countries and Iraq is no exception.